2017
DOI: 10.1021/acs.jcim.7b00244
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Regression and Multiclass Models for Acute Oral Toxicity Prediction with Automatic Chemical Feature Extraction

Abstract: Median lethal death, LD, is a general indicator of compound acute oral toxicity (AOT). Various in silico methods were developed for AOT prediction to reduce costs and time. In this study, we developed an improved molecular graph encoding convolutional neural networks (MGE-CNN) architecture to construct three types of high-quality AOT models: regression model (deepAOT-R), multiclassification model (deepAOT-C), and multitask model (deepAOT-CR). These predictive models highly outperformed previously reported mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(146 citation statements)
references
References 64 publications
1
144
0
1
Order By: Relevance
“…This rapid development is partly stimulated by its many important applications, one of which is drug toxicity prediction in silico [88,127,158]. Together with “Big Data” science [159], machine learning techniques may provide much more information about toxicity than ever before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rapid development is partly stimulated by its many important applications, one of which is drug toxicity prediction in silico [88,127,158]. Together with “Big Data” science [159], machine learning techniques may provide much more information about toxicity than ever before.…”
Section: Discussionmentioning
confidence: 99%
“…The fingerprint was further mined both forwardly and backwardly, which yielded the deep-minded fingerprint (the array of black dots in Figure 3). The deep-minded fingerprint was then tested by the regression model (the blue circle) and the multiclass/multitask models (the green circles), which yielded a classification accuracy up to 95.0% and a regression R square value of 0.861 [127]. …”
Section: Acute (Immediate) Toxicity Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we use multilayer (deep) convolutional neural networks (CNNs) 6 use derived representations to predict perceptual responses neural networks that use ensembles of spatial filters of increasing complexity to to representing objects present in the input Networks based on CNNs are the best performing method for image recognition better at classifying images than performance of CNNs in 2D suggests that they are well types of spatial data, such as the 3D molecular structures. Deep networks have indeed been applied to classify molecules, including the predictions of pharmacokinetics properties, toxicity, and protein ligand interaction [10][11][12] DeepNose: Using artificial neural networks to represent the space of Tran, Daniel Kepple, Sergey Cold Spring Harbor Laboratory, Cold system employs an ensemble of to derive olfactory percepts. W and used that representation to predict human hypothesized that ORs may be considered trained using conventional machine learning called DeepNose, to deduce a low represented by their 3D spatial structure predicting physical properties and odorant percepts found that despite the lack of human expertise, DeepNose features led to perceptual predictions of comparable accuracy to molecular DeepNose network can extract can help understand…”
Section: Tran Daniel Kepple Sergeymentioning
confidence: 99%
“…For instance, the DTI network data have been integrated with the drug structure and protein sequence information into a networkbased machine learning model (e.g., a regularized least squares framework) for predicting new DTIs (Xia et al, 2010;van Laarhoven et al, 2011;van Laarhoven and Marchiori, 2013). Inspired by the recent surge of deep learning techniques, models with higher predictive capacity have also been developed in various drug discovery settings (e.g., compound-protein interaction prediction, drug discovery with one-shot learning) (Wang and Zeng, 2013;Wan and Zeng, 2016;Hamanaka et al, 2017;Tian et al, 2016;Altae-Tran et al, 2017;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%